A Mutation in the G-Protein Gene GNB2 Causes Familial Sinus Node and Atrioventricular Conduction Dysfunction. Issue 10 (12th May 2017) - Stallmeyer, Birgit; Kuß, Johanna; Kotthoff, Stefan; Zumhagen, Sven; Vowinkel, Kirsty; Rinné, Susanne; Matschke, Lina A.; Friedrich, Corinna; Schulze-Bahr, Ellen; Rust, Stephan; Seebohm, Guiscard; Decher, Niels; et al.
Abstract : Rationale: : Familial sinus node and atrioventricular conduction dysfunction is a rare disorder that leads to paroxysmal dizziness, fatigue, and syncope because of a temporarily or permanently reduced heart rate. To date, only a few genes for familial sinus and atrioventricular conduction dysfunction are known, and the majority of cases remain pathogenically unresolved. Objective: : We aim to identify the disease gene in a large 3-generation family (n=25) with autosomal dominant sinus node dysfunction (SND) and atrioventricular block (AVB) and to characterize the mutation-related pathomechanisms in familial SND+AVB. Methods and Results: : Genome-wide linkage analysis mapped the SND+AVB disease locus to chromosome 7q21.1-q31.1 (2-point logarithm of the odds score: 4.64; θ=0); in this region, targeted exome sequencing identified a novel heterozygous mutation (p.Arg52Leu) in the GNB2 gene that strictly cosegregated with the SND+AVB phenotype. GNB2 encodes the β2 subunit (Gβ2 ) of the heterotrimeric G-protein complex that is being released from G-protein–coupled receptors on vagal stimulation. In 2 heterologous expression systems (HEK-293T cells and Xenopus laevis oocytes), an enhanced activation of the G-protein–activated K + channel (GIRK; Kir3.1/Kir3.4) was shown when mutant Gβ2 was coexpressed with Gγ2 ; this was in contrast to coexpression of mutant Gβ2 -Gγ2 with other cardiac ion channels (HCN4, HCN2, and Cav1.2). Molecular dynamics simulations suggested a reduced binding property of mutant Gβ2 to cardiac GIRK channels when compared with native Gβ2 . Conclusions: : A GNB2 gene mutation is associated with familial SND+AVB and leads to a sustained activation of cardiac GIRK channels, which is likely to hyperpolarize the myocellular membrane potential and thus reduces their spontaneous activity. Our findings describe for the first time a role of a mutant G-protein in the nonsyndromic pacemaker disease because of GIRK channel activation. Abstract : Supplemental Digital Content is available in the text.